NANDAI PADA ETNIK SERAWAI DI KABUPATEN SELUMA SEBAGAI SUMBER PEMBELAJARAN APRESIASI SASTRA LAMA - Mareta, Abenda; Agustina, Emi; Sarwono, Sarwit (UNIB Press, 2022)
This study aims (1) to inventory or collect marks on the Serawai ethnicity in Seluma Regency so that it can be a source of learning for the appreciation of old literature. (2) Finding and explaining the moral values ​​contained in the mark of the Serawai ethnicity in Seluma Regency. The method used in this research is a descriptive qualitative method. The data collection technique was carried out by (1) Observation (2) Defect technique (3) Recording (4) Documentation. Data Analysis Techniques (1) perform translation (2) find and explain moral values ​​(3) conclusions. Research Results (1). Until now, markers are still found in 5 sub-districts in Seluma district, although they are no longer told productively because it is difficult to find sources who can still mark, plus many have had health problems and died. The Nandai that was found was the Nandai ghenai which is a type of legend and fairy tale. (2) There are moral messages and values ​​that can be taken in the markings on the Serawai ethnicity such as individual moral values ​​(honest, patient, disciplined, and responsible) and social moral values ​​(respect for every human being, respect for women, respect for the opinions of others , loyal, polite, and true to promises). (3) Nandai can be used as a source of learning appreciation for old literature in Seluma district at the Junior High School, Senior High School, and General levels because it has two languages ​​(Serawai and Indonesian) and Glossary.